An algebra problem by A Former Brilliant Member

Algebra Level 3

If α \alpha and β \beta are roots of x 2 p x + r = 0 x^2-px+r=0 and α 2 \dfrac{\alpha}{2} and 2 β 2\beta are roots of x 2 q x + r = 0 x^2-qx+r=0 . If 3 r 4 = a b ( 2 p q ) ( 2 q p ) \dfrac{3r}{4} = \dfrac ab (2p-q)(2q-p) , where a a and b b are coprime positive integers . Find a + b a+b .


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Rishabh Jain
Jul 3, 2016

Using Vieta's formula: x 2 p x + r = 0 { α + β = p α β = r x^2-px+r=0\small{\begin {cases} \color{#D61F06}{\alpha+\beta=p} \\ \alpha\beta=r\end {cases}} x 2 q x + r = 0 { α 2 + 2 β = q α + 4 β = 2 q α β = r x^2-qx+r=0\small{ \begin {cases}\dfrac{\alpha}2+2\beta=q\implies \color{#D61F06}{\alpha+4\beta=2q }\\ \alpha\beta=r\end {cases}}

Solving α + β = p \color{#D61F06}{\alpha+\beta=p} and α + 4 β = 2 q \color{#D61F06}{\alpha+4\beta=2q } for α \alpha and β \beta , we get:

α = 2 ( 2 p q ) 3 , β = 2 q p 3 \alpha= \dfrac{2(2p-q)}3, \beta=\dfrac{2q-p}3

r = α β = 2 ( 2 q p ) ( 2 p q ) 9 \therefore r=\alpha\beta=\dfrac{2(2q-p)(2p-q)}9

3 4 × 2 9 = 1 6 \LARGE\therefore \dfrac 34\times \dfrac{2}9=\dfrac 16

1 + 6 = 7 \huge \therefore 1+6=\boxed 7

Hung Woei Neoh
Jul 3, 2016

x 2 p x + r = 0 x^2-px+r=0 has roots α \alpha and β \beta . From Vieta's formula, we have

α + β = p α β = r \alpha+\beta=p\\ \alpha\beta=r

x 2 q x + r = 0 x^2-qx+r=0 has roots α 2 \dfrac{\alpha}{2} and 2 β 2\beta . From Vieta's formula:

α 2 + 2 β = q α β = r \dfrac{\alpha}{2}+2\beta=q\\ \alpha\beta=r

Given that

3 r 4 = k ( 2 p q ) ( 2 q p ) 3 α β 4 = k ( 2 ( α + β ) ( α 2 + 2 β ) ) ( 2 ( α 2 + 2 β ) ( α + β ) ) 3 α β 4 = k ( 2 α + 2 β α 2 2 β ) ( α + 4 β α β ) 3 α β 4 = k ( 3 α 2 ) ( 3 β ) k = ( 3 α β 4 2 ) ( 2 3 α ) ( 1 3 β ) = 1 6 \dfrac{3r}{4}=k(2p-q)(2q-p)\\ \dfrac{3\alpha\beta}{4}=k\Big(2(\alpha+\beta)-(\dfrac{\alpha}{2}+2\beta)\Big)\Big(2(\dfrac{\alpha}{2}+2\beta)-(\alpha+\beta)\Big)\\ \dfrac{3\alpha\beta}{4}=k\Big(2\alpha+2\beta-\dfrac{\alpha}{2}-2\beta\Big)\Big(\alpha+4\beta-\alpha-\beta\Big)\\ \dfrac{3\alpha\beta}{4}=k\Big(\dfrac{3\alpha}{2}\Big)\Big(3\beta\Big)\\ k=\left(\dfrac{\color{#3D99F6}{\cancel{\color{#333333}{3\alpha}}}\color{#EC7300}{\cancel{\color{#333333}{\beta}}}}{\color{#D61F06}{\cancel{\color{#333333}{4}}2}}\right)\left(\dfrac{\color{#D61F06}{\cancel{\color{#333333}{2}}}}{\color{#3D99F6}{\cancel{\color{#333333}{3\alpha}}}}\right)\left(\dfrac{1}{3\color{#EC7300}{\cancel{\color{#333333}{\beta}}}}\right)\\=\dfrac{1}{6}

a = 1 , b = 6 , a + b = 1 + 6 = 7 a=1,\;b=6,\;a+b=1+6=\boxed{7}

nice, +1 same solution

Novril Razenda - 4 years, 11 months ago

Using Vieta formulas , we have:

{ α + β = p . . . ( 1 ) α 2 + 2 β = q . . . ( 2 ) α β = r . . . ( 3 ) \begin{cases} \alpha + \beta = p & ...(1) \\ \dfrac \alpha 2 + 2 \beta = q & ...(2) \\ \alpha \beta = r & ...(3) \end{cases}

2 ( 2 ) ( 1 ) : 3 β = 2 q = q β = 1 3 ( 2 q p ) \begin{aligned} 2(2)-(1): \quad 3 \beta & = 2q = q \\ \implies \beta & = \frac 13 (2q-p) \end{aligned}

( 1 ) : α = p 1 3 ( 2 q p ) = 2 3 ( 2 p q ) \begin{aligned} (1): \quad \alpha & = p - \frac 13 (2q-p) \\ & = \frac 23 (2p-q) \end{aligned}

3 4 ( 3 ) : 3 4 r = 3 4 α β = 3 4 2 3 ( 2 q p ) 1 3 ( 2 q p ) = 1 6 ( 2 p q ) ( 2 q p ) \begin{aligned} \frac 34 (3): \quad \frac 34 r & = \frac 34 \alpha \beta \\ & = \frac 34 \cdot \frac 23 (2q-p) \cdot \frac 13 (2q-p) \\ & = \frac 16 (2p-q)(2q-p) \end{aligned}

a + b = 1 + 6 = 7 \implies a+b = 1 +6 = \boxed{7}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...